MAVS: A Two-Sided CARD Mediating Antiviral Innate Immune Signaling and Regulating Immune Homeostasis - Chen, Yunqiang; Shi, Yuheng; Wu, Jing; Qi, Nan (Frontiers in Microbiology, 2021)
Mitochondrial antiviral signaling protein (MAVS) functions as a switch in the immune signal transduction against most RNA viruses. Upon viral infection, MAVS forms prion-like aggregates by receiving the cytosolic RNA sensor RIG-I activated signaling and further activates/switches on the type I interferon (IFN-I) signaling. While under resting state, MAVS is prevented from spontaneously aggregating to switch off the signal transduction and maintain immune homeostasis. Due to the dual role in antiviral signal transduction and immune homeostasis, MAVS has emerged as the central regulation target by both viruses and hosts. Recently, researchers show increasing interest in viral evasion strategies and immune homeostasis regulations targeting MAVS, especially focusing on the post-translational modifications of MAVS such as ubiquitination and phosphorylation. This review summarizes the regulations of MAVS in antiviral innate immune signaling transduction and immune homeostasis maintenance.